Financial Risk Protection for Neurosurgical Care in Indonesia and the Philippines: A Primer on Health Financing for the Global Neurosurgeon - Ferraris, Kevin Paul; Yap, Maria Eufemia C.; Bautista, Maria Cristina G.; Wardhana, Dewa Putu Wisnu; Maliawan, Sri; Wirawan, I Made Ady; Rosyidi, Rohadi Muhammad; Seng, Kenny; Navarro, Joseph Erroll (Frontiers in Surgery, 2021)
Which conditions treated by neurosurgeons cause the worst economic hardship in low middle-income in countries? How can public health financing be responsive to the inequities in the delivery of neurosurgical care? This review article frames the objectives of equity, quality, and efficiency in health financing to the goals of global neurosurgery. In order to glean provider perspectives on the affordability of neurosurgical care in low-resource settings, we did a survey of neurosurgeons from Indonesia and the Philippines and identified that the care of socioeconomically disadvantaged patients with malignant intracranial tumors were found to incur the highest out-of-pocket expenses. Additionally, the surveyed neurosurgeons also observed that treatment of traumatic brain injury may have to require greater financial subsidies. It is therefore imperative to frame health financing alongside the goals equity, efficiency, and quality of neurosurgical care for the impoverished. Using principles and perspectives from managerial economics and public health, we conceptualize an implementation framework that addresses both the supply and demand sides of healthcare provision as applied to neurosurgery. For the supply side, strategic purchasing enables a systematic and contractual management of payment arrangements that provide performance-based economic incentives for providers. For the demand side, conditional cash transfers similarly leverages on financial incentives on the part of patients to reward certain health-seeking behaviors that significantly influence clinical outcomes. These health financing strategies are formulated in order to ultimately build neurosurgical capacity in LMICs, improve access to care for patients, and ensure financial risk protection.